2011
DOI: 10.1017/s0014479710000931
|View full text |Cite
|
Sign up to set email alerts
|

THE WATER RELATIONS AND IRRIGATION REQUIREMENTS OF COCONUT (Cocos nucifera): A REVIEW

Abstract: SUMMARYThe results of research on the water relations and irrigation needs of coconut are collated and summarized in an attempt to link fundamental studies on crop physiology to drought mitigation and irrigation practices. Background information on the centres of origin and production of coconut and on crop development processes is followed by reviews of plant water relations, crop water use and water productivity, including drought mitigation. The majority of the recent research published in the international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 40 publications
1
30
0
2
Order By: Relevance
“…Even if we take the higher part of the irrigation requirement, approximately 100 L of water per palm per day could be saved, and if the quantum is converted for the entire coconut irrigated area, it will be a saving of a huge quantity of water at a state level. Carr [1] summarized the water relations and irrigation requirements of coconut by daily water use from various studies carried out around the globe, and indicated a range of 75 to 220 L per palm per day, which is nearer to our current findings. The current recommendation of the Kerala Agricultural University is on the higher side, when compared with the output from the current study [32].…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Even if we take the higher part of the irrigation requirement, approximately 100 L of water per palm per day could be saved, and if the quantum is converted for the entire coconut irrigated area, it will be a saving of a huge quantity of water at a state level. Carr [1] summarized the water relations and irrigation requirements of coconut by daily water use from various studies carried out around the globe, and indicated a range of 75 to 220 L per palm per day, which is nearer to our current findings. The current recommendation of the Kerala Agricultural University is on the higher side, when compared with the output from the current study [32].…”
Section: Resultssupporting
confidence: 64%
“…Even though coconut is found mainly in coastal areas, it can grow in various soils with different moisture conditions and regimes. In Kerala, it is mostly grown in laterite/lateritic soils of the ultisol order (gravelly soils), which are prone to drought and are frequently exposed to intermittent moisture shortfall throughout the summer season [1]. This moisture deficit during its growth stage has a serious impact on its productivity [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the identification and validation of reference genes for qPCR gene expression studies is critical. In previous research on water relations and irrigation needs in C. nucifera, a crop physiology approach to drought stress was undertaken with measurements such as proline concentration, osmotic potential, leaflet water potential, and leaflet pigment concentration (Carr 2011;Gomes et al 2008Gomes et al , 2010Hebbar et al 2013). In applying molecular biology research techniques to understand coconut stress responses, selection and validation of suitable reference genes for gene expression analysis will comprise an important first step.…”
Section: Discussionmentioning
confidence: 99%
“…Especialmente las complejas redes de raíces dan cohesión a los sedimentos y pueden disminuir el impacto de estos eventos. El sistema de raíces de la palma de coco (Cocos nucifera L.) varía según el sustrato en el que se encuentre: en tierra firme la longitud de las raíces alcanza 5 m y en substratos arenosos 7 m. Las raíces pueden ocupar un radio de ~6 m, y como sistema de anclaje de la palma permite la retención efectiva del sustrato donde crece (Carr, 2011).…”
unclassified